Editor's Note - Isa, Mansor; K. Suppiah, Susela Devi (Asian Journal of Business and Accounting, 2017)
As the year 2017 is about to come to its full cycle, we are proud to present you with the second issue of Volume 10 of the Asian Journal of Business and Accounting (AJBA). This is a special issue to commemorate the 10th anniversary of AJBA. Since its debut in 2008, AJBA has continued to publish contributions which focus on the issues of business and accounting that impact the Asian region. We are encouraged by the growing interest of these scholars from various parts of the world including the Asian region. As institutions of higher learning in the Asian region join the race to improve their ranking, the demand for journal space is also ever increasing. In this regard, AJBA is serious about its role as a vehicle for disseminating the region’s academic research findings in a timely manner. AJBA has been indexed in the Emerging Sources Citation Index, Scopus, ERA, Asian Citation Index and MyCite. Through its ten years existence, AJBA has steadily maintained its rigour and quality; and we are proud that AJBA has achieved its ranking status. In this special issue, a total of ten articles are presented. The authors are from Bangladesh, Ghana, India, Indonesia, Lebanon, Jordan, Saudi Arabia, Malaysia and Thailand. Although many of the articles are multi-disciplinary, three common themes emerge: Capital Market issues (Acaranupong; Owusu, Saat, Suppiah, & Law; Das & Barai); Ethical and Social Behaviour (Hossain, Ahmad, & Siraj; Septiari & Maruli; Nordin, Muhammad, Wahab, & Yaakub; Rustiarini & Sunarsih; Duarsa & Riantoputra) and Technology (Dbouk & Zaarour; Rawashdeh & Al-namlah). The first paper by Acaranupong is timely, in view of the growing global interest towards fair value measurement, with the International Financial Reporting Standards (IFRS) 13 on Fair Value Measurement. Focusing on the capital market in Thailand, the paper demonstrates that the cost model of accounting for investment properties has higher value relevance when compared to the fair value model. The choice of fair value or cost model appears to be influenced by profitability and firm size. This calls for future studies to examine and compare the accounting practices and value relevance of investment properties in other countries. Using a dynamic panel analysis of data from 116 developing countries, Owusu, Saat, Suppiah, and Law provide a global analysis of the role of institutional quality in the relationship between IFRS adoption and foreign direct investment inflows. Their paper offers evidence to show that IFRS adoption matters only when the institutional quality is high. This sends a sound message to regulators in emerging countries that mere IFRS adoption is insufficient because macro economic variables are critical, one of which is institutional quality. As one of the world’s fastest growing economy, India’s foreign institutional investments have also grown in tandem. Thus, it is significant for both the academics and practitioners to understand the cross sectional behaviour of stock returns in the Indian market. This is manifested in the third paper by Das and Barai who examine the role of non-marketable assets in the composition of market proxies for an asset pricing model in India. In recent years, there is a growing expectation from investors for companies to practice corporate social responsibility (CSR). Thus, disclosure of the companies’ CSR activities can enhance their corporate image and impress investors. In the fourth paper, Hossain, Ahmad, and Siraj identify the persuasive strategies employed by Bangladeshi companies in disclosing poverty related CSR activities in their annual reports. Their paper suggests that Bangladeshi firms’ disclosure is rather rhetoric in nature. The authors assert that there is a need for regulators to institute appropriate regulations so as to ensure balanced disclosure practices. The profitability of a company is imperative to investors. This results in the temptation to employ earnings management strategies in order to report higher profits. In the next paper, Septiari and Maruli employ an experimental research design to investigate whether partici-pants with higher level of professional commitment are less/more likely to engage in earnings management as well as whether pressure (either legal consequences or instructions) plays a role in this relationship. This paper brings an interesting facet to earnings management research. Since some businesses may under-report their taxable income to the tax authorites, it is important that tax audits are carried out to verify the accuracy of the tax returns. The sixth paper by Nordin, Muhammad, Wahab, and Yaakub, focuses on the tax auditors’ conciliatory style in dealing with tax disputes in Malaysia. The study shows that factors such as taxpayers’ cooperation, tax complexity and the extant of managerial control can impact tax auditors’ conciliatory style. The Inland Revenue Board may find their results useful in reviewing its process of dispute resolution. Illegal or unethical practices occur not only in the corporate world, but also in the public sector. Thus, the role of the auditors in discovering and disclosing these practices should not be ignored. In the seventh paper, Rustiarini and Sunarsih draw on the Theory of Planned Behaviour, to evidence the factors influencing whistleblowing behaviours amongst government auditors in Indonesia. The study highlights the individual traits of the auditors in pursuing this task. Future research may want to focus on organisational and institutional settings so as to complement this issue in the Indonesian context. The following paper concerntrates on technology which is indis-pensable in today’s world. Dbouk and Zaarour draw on a supervised machine learning approach to detect earnings manipulation. The study shows the superior ability of machine learning thereby, highlighting the importance of technology; it also contributes to the body of current literature on digital economy. In the next paper, Rawashdeh and Al-namlah investigate the factors influencing the intention of small and medium enterprises (SMEs) in Saudi Arabia in adopting electronic data interchange (EDI). Their paper shows that perceived EDI benefits, organisational readiness, government support and pressure from business partners are significant factors influencing EDI adoption. It is suggested that industry practitioners develop comprehensive business strategies and institutionalise policies so as to facilitate the EDI implementation in Saudi Arabia. Organisations not only require the latest technology to prosper in today’s world; they also need good leadership. The final paper by Duarsa and Riantoputra, investigates the Leader-Member Exchange (LMX) as a mediator of the relationship between benevolence value and leader effectiveness. Interestingly, their paper confirms that sub-ordinates exhibit the benevolent value when they perceive good feelings about their leaders. We take this opportunity to thank all the members of the editorial and advisory board, reviewers and contributors, for their continued support and encouragement. We are very grateful to Chan Wai Meng for her drive, commitment, passion and perseverance in managing the journal and also for bringing this journal to this level. We also appreciate the editorial and advisory boards for requesting us, the former Editors-in-Chief of AJBA, to be guest editors for this special issue of AJBA. We hope this issue brings AJBA another step closer to be a leading journal for Asian scholars.